Business diplomacy by multinational corporations : towards a model based on Catholic social thought - Ruël, Huub (Emerald points., 2022)
Over the past two decades, increasing attention has been paid to the concept of business diplomacy. This is becoming more important for multinational corporations (MNCs) as they deal with an increasingly demanding and dynamic international business arena. Despite the growing literature on this phenomenon, there is no sound theory-based business diplomacy model that can help to understand MNCs' relationship-building activities in the global society and provide a normative, moral guide for MNCs on how to conduct business diplomacy successfully. In Business Diplomacy by Multinational Corporations, Huub Ruël turns to Catholic Social Thought (CST), an intellectual tradition extending back 2000 years that promotes the key principles of human dignity, the common good, solidarity and subsidiarity. According to CST, a business is a community of people and its purpose is to serve the common good. This clearly diverges from the dominant shareholder view of business and CST provides a basis for a normative business diplomacy model. This in turn provides a clear, distinctive instrument for MNCs to reflect on their purpose and role in the global society while also guiding and directing their relationship-building actions with other actors in the global society. This book is essential reading for researchers studying ethics and morality from an international business viewpoint.